Bangerter filter’s role in regulating ocular axial length: a novel application of an established therapy - Jingjing Jiang; Tong Zhao; Yue Yin; Mengyu Han; Xi Wu; Yi Chen (European Journal of Medical Research)
Abstract Key messages What is known Occlusion with Bangerter filters designed with different translucent microscopic diffusers is an effective treatment for anisometropic amblyopia. What is new Bangerter filters were found to show an effect on slowing down ocular axial length (AL) growth. When rapid hyperopic reduction occurs in the non-amblyopic eye combined with persistently widening interocular AL differences, Bangerter filter application represents a more preferable alternative to patching for managing anisometropic amblyopia. Purpose Bangerter filter occlusion is an effective clinical method for amblyopia treatment. This study aimed to compare the nonamblyopic eyes elongation and refraction change of patching and Bangerter filter occlusion in treating patients with anisometropic amblyopia and to further investigate the effect of Bangerter filter on axial length growth. Methods This retrospective study included 54 patients with anisometropic amblyopia categorized by initial treatment: patching group (n = 24) and Bangerter filter group (n = 30). Consecutive records of both the amblyopia and nonamblyopia eyes were reviewed from baseline before treatment onset to follow-up visits during or post-treatment, including best corrected visual acuity, pneumatic intraocular pressure, spherical equivalent refraction (SER), axial length (AL), corneal curvature, binocular visual function, and accommodative function. In addition, macrostructures of three different densities of Bangerter filters and diffusion optics technology lenses were observed and compared. Results The nonamblyopic eyes in the Bangerter filter group had significantly lower AL increases from baseline (− 0.15 and − 0.20, respectively, P < 0.05) and significantly fewer SER reductions from baseline (0.45 and 0.57, respectively, P < 0.05) compared with the patching group at both two follow-up visits. The interocular AL difference between nonamblyopic and amblyopic eyes increased by 0.15 ± 0.27 mm in the occlusion group at the second follow-up (from baseline 0.23 ± 0.61 mm to second follow-up 0.38 ± 0.69 mm, P = 0.004), while it decreased by 0.18 ± 0.20 mm in the Bangerter filter group at the second follow-up (from baseline 0.72 ± 0.68 mm to second follow-up 0.54 ± 0.69 mm, P < 0.001). Conclusions Bangerter filter, as a traditional occlusion therapy, have been shown to effectively slow ocular AL growth thereby reducing interocular axial length disparity when compared to patching therapy in anisometropic amblyopia treatment. Rapid reduction of hyperopic refraction in non-amblyopic eyes combined with persistent increases in interocular AL difference may constitute a novel indication for Bangerter filter application.